2013
DOI: 10.19026/rjaset.5.4430
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Customization, Price, Geographical Accessibility, Professional Knowledge and Interaction on Intent of Customers for Using Internet Banking Services in Iran

Abstract: Not all organizations and institutions are equally successful in employing electronic commerce. Thus it is necessary to conduct required studies so that we can create a favorable policy in relation to implementation and employment of electronic commerce and identify factors which facilitate its growth. Thus, the purpose of this study is to investigate the effects of customization, price, geographical accessibility, professional knowledge and interaction on intent of customers for using internet banking service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…According to Alalwan et al (2017), users tend to compare the utilities received and the financial cost of using a new technology and increase their level of usage when they are rewarded with discounts. Ghalandari (2013) showed that price has a positive effect on the intention to use internet banking services, whereas Chaudary et al (2014) found that price has a positive significant relation with purchase intention. Phan and Mai (2016) further proved that price exercises a positive impact on purchase intention.…”
Section: Pricementioning
confidence: 97%
“…According to Alalwan et al (2017), users tend to compare the utilities received and the financial cost of using a new technology and increase their level of usage when they are rewarded with discounts. Ghalandari (2013) showed that price has a positive effect on the intention to use internet banking services, whereas Chaudary et al (2014) found that price has a positive significant relation with purchase intention. Phan and Mai (2016) further proved that price exercises a positive impact on purchase intention.…”
Section: Pricementioning
confidence: 97%